Trends des Verkehrsverhaltens in den USA und in Deutschland. - Bühler, Ralph; Kunert, Uwe (Deutscher Verkehrs-Verl., 2010)
Schon seit Jahrzehnten werden ökonomische und gesellschaftliche Entwicklungen in den USA von Europa aus mit Interesse beobachtet, verbunden mit der Frage, ob diese auch hier eintreten werden. Für den Mobilitätssektor interessierte die Frage, ob ähnliche Motorisierungskennziffern, Verkehrsmittelanteile und Verkehrsleistungen im Zuge der weiteren Entwicklung zu erwarten sind. Frühere Prognosen des Pkw-Bestandes orientierten sich in der Abschätzung eines möglichen Sättigungsniveaus der Motorisierung nicht selten an den USA und erwarteten eine Annäherung der Motorisierungskennziffern.

The article describes and compares trends in daily travel behavior in Germany and the USA since 1960. The analysis shows that both countries have witnessed sharp increases in automobile ownership and use over the last 40 years. In both countries average trip distances and the number of daily trips per person have also increased significantly. Moreover, the share of trips by public transport, bicycle, and on foot has declined in both countries. Nonetheless, in 2001/2002 Americans still owned 41 % more cars per capita, made 25 % more trips per day, and traveled more than twice as many kilometers by car annually than Germans. In 2002, the car accounted for 86 % of all trips in the USA, compared to 61 % in Germany. Compared to Germans, Americans made a four times lower share of trips by public transport (1.6 % in the USA vs. 8.0 % in Germany), were ten times less likely to ride their bicycle (0.8 % vs. 9.0 %), and walked for a two-and-a-half times lower share of trips (9 % vs. 23 %). We conclude that both countries show similar trends towards more motorization, but that automobile use is still on distinct different levels in the two countries.
Trends of travel behavior in the USA and in Germany.
Keywords: Individualverkehr; Mobilität; Verkehrsverhalten; Motorisierung; Personenkraftwagen; Verkehrsnachfrage; Verkehrsmittelwahl; Verkehrsstatistik; Verkehrspolitik; Fahrleistung; Verkehrsleistung; Alltagsverkehr; Kennziffer; Trend